Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2020)
There is one thing in my opinion that is constant in life, and that is change. 2020, has been just that… a year of change driven by a global health crisis and a new way of caring. We have been asked, almost daily at the beginning, to change our activities at home and work. We have taken the healthcare principles of cleanliness and sanitation, contact and transmission, to new levels. We have stepped up, we have changed, and we have succeeded.